Preparation method of PVDF hybrid membrane for oil-water separation
By hybridizing the polyethylene glycol-functionalized SiO2 nanoparticles with PVDF powder and treating them in dopamine buffer solution, a PVDF/SiO2-g-PEGDA/PDA hybrid film with ultra-hydrophilic and underwater super-oleophobic properties was prepared, which solved the pollution and permeability of the existing membranes when treating oil-containing wastewater, and achieved efficient oil-water separation.
Patent Information
- Application Number
- CN202510189568.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-04-15
AI Technical Summary
When treating oil-containing wastewater, the existing PVDF powder oil-water separation membrane is susceptible to oil contamination, resulting in a decrease in separation flux and a decrease in separation efficiency. The permeability of the membrane is affected by the load of nanoparticles, and the degree of channel modification is limited.
Polyethylene glycol-functionalized SiO2 nanoparticles were synthesized by photo-induced thiol-ethylene glycol-functionalized SiO2 nanoparticles were prepared by water vapor-induced phase conversion method, and then treated in a buffer solution of dopamine to form a hydrophilized PVDF/SiO2-g-PEGDA/PDA hybrid film.
The prepared PVDF/SiO2-g-PEGDA/PDA hybrid film has good hydrophilicity, controllable structure and permeability, significantly improves the oil-water separation efficiency, avoids oil pollution, and has a simple process and low cost.
Smart Images

Figure CN119819143A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of membrane technology, and in particular relates to a method for preparing a PVDF hybrid membrane for oil-water separation. Background Art
[0002] Oily wastewater is widely present in many industries such as petrochemicals, food processing, and energy metallurgy. The direct discharge of oily wastewater will cause serious pollution problems. Traditional separation methods such as air flotation and gravity separation are difficult to effectively treat oily wastewater. Especially for emulsified oil wastewater, the separation efficiency is lower. Membrane separation technology has the characteristics of high separation efficiency, low energy consumption, and no secondary pollution. It shows great application prospects in the field of oily wastewater treatment, but traditional polymer membranes are easily contaminated by oil substances when treating oily wastewater, resulting in reduced separation flux and decreased separation efficiency.
[0003] In recent years, the field of oil-water separation of superhydrophilic / underwater superoleophobic polyvinylidene fluoride (PVDF powder) separation membrane materials has received extensive attention. The hydrophilic functional groups on the membrane surface can tightly bind water molecules through hydrogen bonds or electrostatic effects to form a hydration layer, prevent the adhesion of oil substances, and play an anti-pollution role. Qi Liang et al. applied DA and carboxylated covalent organic framework nanoparticles on the surface of PVDF powder membrane to achieve superhydrophilic modification (ACS Appl. Mater. Interfaces 2022, 14, 45880-45892). The modified membrane is used for the separation of oil-in-water emulsions and exhibits good oil resistance. Although the membranes prepared by these methods have good oil-water separation performance and anti-pollution performance, since nanoparticles are usually coated on the membrane surface, the degree of modification of the membrane body pores is limited. Secondly, the permeability of the membrane is often affected by the loading amount of nanoparticles. When the loading amount is too high, the membrane pores will be blocked, which will weaken the permeability of the separation membrane.
[0004] Therefore, how to prepare PVDF powder separation membrane with good hydrophilicity and controllable structure and permeability has become an urgent problem to be solved. Summary of the invention
[0005] In order to break through the technical bottleneck of existing PVDF powder oil-water separation membrane materials, the present invention proposes a method for preparing a PVDF hybrid membrane for oil-water separation. The PVDF hybrid membrane for oil-water separation of the present invention has good hydrophilicity and controllable structure and permeability.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention:
[0008] A method for preparing a PVDF hybrid membrane for oil-water separation comprises the following steps:
[0009] Polyethylene glycol-functionalized SiO2 (silicon dioxide) nanoparticles were synthesized by photoinitiated thiol-ene stepwise polymerization.
[0010] PVDF powder (polyvinylidene fluoride) and the polyethylene glycol-functionalized SiO2 nanoparticles are prepared into a casting solution, and a primary hybrid membrane is prepared by a water vapor-induced phase inversion method. The primary hybrid membrane is immersed in a tris(hydroxymethyl)aminomethane hydrochloride (Tris-HCl) buffer solution containing dopamine (DA) to obtain the PVDF hybrid membrane for oil-water separation (PVDF / SiO2-g-PEGDA / PDA hybrid membrane).
[0011] Further, the steps of synthesizing polyethylene glycol functionalized SiO2 nanoparticles are as follows:
[0012] Treat SiO2 nanoparticles with 3-mercaptopropyltriethoxysilane (MPTS) to obtain thiolated SiO2 nanoparticles (SiO2-SH);
[0013] Anhydrous ethanol is added to the SiO2-SH, and after uniform mixing, polyethylene glycol diacrylate (PEGDA), hexanediol (HD) and 2-dimethoxy-2-phenylacetophenone (DMPA) are added, and the mixture is reacted under ultraviolet conditions in a nitrogen atmosphere to synthesize polyethylene glycol-functionalized SiO2 nanoparticles (SiO2-g-PEGDA).
[0014] The invention firstly treats SiO2 nanoparticles with 3-mercaptopropyltriethoxysilane (MPTS) to obtain thiolated SiO2 nanoparticles (SiO2-SH), and then uses polyethylene glycol diacrylate (PEGDA) and hexanedithiol (HD) as monomers and 2,2-dimethoxy-2-phenylacetophenone (DMPA) as a photosensitizer to synthesize polyethylene glycol functionalized silica nanoparticles (SiO2-g-PEGDA) through a thiol-ene photochemical reaction. The prepared SiO2-g-PEGDA is hybridized with polyvinylidene fluoride (PVDF powder), and a primary membrane is prepared by a water vapor induced phase conversion method, and then immersed in a tris (hydroxymethyl) aminomethane hydrochloride (Tris-HCl) buffer solution of dopamine (DA) for treatment to obtain a PVDF hybrid membrane for oil-water separation (PVDF / SiO2-g-PEGDA / PDA hybrid membrane). In the present invention, the introduction of hydrophilic SiO2-g-PEGDA is combined with dopamine biomimetic coating modification, so that the hybrid membrane has superhydrophilic / underwater superoleophobic properties.
[0015] The mass ratio of the SiO2 nanoparticles to the MPTS is (1-10): (5-50);
[0016] And / or, when SiO2 nanoparticles are treated with MPTS: the treatment temperature is 80°C-120°C, and the treatment time is 12h-48h.
[0017] The mass ratio of SiO2-SH, PEGDA, HD and DMPA is (10-100):(25-100):(25-100):(0.5-2).
[0018] The molecular weight of the PEGDA is 200 g / mol-2000 g / mol.
[0019] When reacting under ultraviolet conditions: the power of ultraviolet light is 10w-60w, and the reaction time is 2h-8h.
[0020] Furthermore, the synthesis method of the SiO2-g-PEGDA is as follows: weigh SiO2 nanoparticles, place them in toluene, and ultrasonically disperse them for 30 minutes to obtain a suspension of 10g / L-100g / L; add 3-mercaptopropyltriethoxysilane (MPTS) to the suspension, the concentration of MPTS in the reaction mixture is 50g / L-500g / L, react at 80°C-120°C for 12-48h, after the reaction is completed, centrifuge and wash three times with anhydrous ethanol, and dry to obtain thiolated SiO2 nanoparticles (SiO2-SH); place SiO2-SH in a quartz reaction flask, add anhydrous ethanol and ultrasonically disperse it, then add hexamethylenedithiol (HD), polyethylene glycol diacrylate (PEGDA) and 2 , 2-dimethoxy-2-phenylacetophenone (DMPA), the reaction mixture (the concentration of SiO2-SH in the reaction mixture is 10g / L-100g / L, the concentration of HD monomer in the reaction mixture is 25g / L-100g / L, the concentration of PEGDA monomer in the reaction mixture is 25g / L-100g / L, the molecular weight of PEGDA monomer is 200g / mol-2000g / mol, and the concentration of DMPA in the reaction mixture is 0.5g / L-2g / L) is filled with nitrogen for 15 minutes, and then placed under ultraviolet light at 10w-60w for 2h-8h. After the reaction, the product is centrifuged and washed three times with anhydrous ethanol to obtain SiO2-g-PEGDA, which is a nanoparticle.
[0021] Furthermore, the step of preparing the PVDF powder and the SiO2-g-PEGDA into a casting solution is as follows: placing the SiO2-g-PEGDA in N-methylpyrrolidone (NMP), ultrasonically dispersing it, adding the PVDF powder, heating to dissolve it, and standing to degas to obtain the casting solution.
[0022] The content of SiO2-g-PEGDA in the casting solution is 0.2wt%-3wt%, and the content of PVDF powder in the casting solution is 12wt%-20wt%.
[0023] Furthermore, the steps of preparing a hybrid membrane using PVDF powder and SiO2-g-PEGDA are as follows: placing SiO2-g-PEGDA nanoparticles in N-methylpyrrolidone (NMP), ultrasonically dispersing, adding PVDF powder, heating at 60°C to dissolve, and standing for degassing for 24 hours to obtain a cast film, wherein the content of SiO2-g-PEGDA in the casting liquid is 0.2wt%-3wt%, and the content of PVDF powder in the casting liquid is 12wt%-20wt%; dropping the above casting liquid on a clean glass plate, and scraping with a film having a thickness of 50μm-500μm The liquid flat membrane was obtained by scraping with a knife, and the liquid flat membrane was immediately transferred to an artificial climate box (the temperature in the artificial climate box was 20°C-50°C, and the humidity was 30%-100%). After 10min-30min, the liquid flat membrane was taken out together with the glass plate, and immersed in a tris-HCl buffer solution of dopamine (DA) with a concentration of 0.5g / L-4g / L, and reacted at room temperature for 6h-48h. After taking out, a PVDF hybrid membrane for oil-water separation was obtained, which was recorded as PVDF / SiO2-g-PEGDA / PDA hybrid membrane.
[0024] The second technical solution of the present invention:
[0025] The present invention also provides a PVDF hybrid membrane for oil-water separation prepared according to the method.
[0026] The third technical solution of the present invention:
[0027] The present invention also provides application of the above PVDF hybrid membrane for oil-water separation in oil-water separation.
[0028] Compared with the prior art, the present invention has the following advantages and technical effects:
[0029] The present invention uses a light-initiated mercapto-ene stepwise polymerization method to graft hydrophilic PEGDA onto SiO2 nanoparticles to obtain SiO2-g-PEGDA nanoparticles; the nanoparticles are further hybridized with PVDF powder, a flat membrane is prepared by a water vapor-induced phase conversion method, and after being immersed in a dopamine buffer solution for treatment, a hydrophilized hybrid membrane PVDF / SiO2-g-PEGDA / PDA is obtained. The hybrid membrane of the present invention has the characteristics of simple process and low cost, and the prepared hydrophilized hybrid membrane can be used as a sewage treatment separation membrane, and is particularly suitable for oil-water separation. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0031] Figure 1 is an infrared spectrum of SiO2 nanoparticles, SiO2-SH nanoparticles and SiO2-g-PEGDA nanoparticles in Example 1 of the present invention;
[0032] Figure 2 This is a surface SEM image of the pure PVDF membrane prepared in Comparative Example 1 of the present invention;
[0033] Figure 3 This is a surface SEM image of the PVDF / SiO2-g-PEGDA0.1 membrane prepared in Comparative Example 3 of the present invention;
[0034] Figure 4 This is a surface SEM image of the PVDF / SiO2-g-PEGDA0.1 / PDA membrane prepared in Example 2 of the present invention;
[0035] Figure 5 This is a surface SEM image of the PVDF / SiO2-g-PEGDA0.2 / PDA membrane prepared in Example 3 of the present invention;
[0036] Figure 6 The pure water dynamic contact angle of the membranes prepared in Examples 1-3 and Comparative Examples 1-3 of the present invention;
[0037] Figure 7 This is a photograph of the pump oil emulsion before separation using the PVDF / SiO2-g-PEGDA0.1 / PDA membrane prepared in Example 2 of the present invention;
[0038] Figure 8 This is a photograph of the pump oil emulsion after separation using the PVDF / SiO2-g-PEGDA0.1 / PDA membrane prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0039] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0040] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0041] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0042] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0043] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0044] The embodiment of the present invention provides a method for preparing a PVDF hybrid membrane for oil-water separation: first, SiO2 nanoparticles are treated with 3-mercaptopropyltriethoxysilane (MPTS) to obtain thiolated SiO2 nanoparticles (SiO2-SH), and then polyethylene glycol diacrylate (PEGDA) and hexamethylenethiol (HD) are used as monomers and 2,2-dimethoxy-2-phenylacetophenone (DMPA) is used as a photosensitizer to synthesize polyethylene glycol-functionalized silica nanoparticles (SiO2-g-PEGDA) through a thiol-ene photochemical reaction; the prepared SiO2-g-PEGDA is hybridized with polyvinylidene fluoride (PVDF) powder, and a primary membrane is prepared by a water vapor-induced phase inversion method, and then immersed in a tris(hydroxymethyl)aminomethane hydrochloride (Tris-HCl) buffer solution of dopamine (DA) for treatment to obtain a PVDF hybrid membrane for oil-water separation (PVDF / SiO2-g-PEGDA / PDA hybrid membrane). In the present invention, the introduction of hydrophilic SiO2-g-PEGDA is combined with dopamine biomimetic coating modification, so that the hybrid membrane has superhydrophilic / underwater superoleophobic properties.
[0045] In some embodiments of the present invention, the synthesis method of SiO2-g-PEGDA is as follows: weigh SiO2 nanoparticles, place them in toluene, and ultrasonically disperse them for 30 minutes to obtain a suspension of 10g / L-100g / L; add 3-mercaptopropyltriethoxysilane (MPTS) to the suspension, the concentration of MPTS in the reaction mixture is 50g / L-500g / L, react at 80°C-120°C for 12-48h, after the reaction is completed, centrifuge and wash three times with anhydrous ethanol, and dry to obtain thiolated SiO2 nanoparticles (SiO2-SH); place SiO2-SH in a quartz reaction flask, add anhydrous ethanol and ultrasonically disperse it, then add hexamethylenedithiol (HD), polyethylene glycol diacrylate (PEGDA) and 2,2-dimethoxy-2-phenylacetophenone (DMPA), the reaction mixture (the concentration of SiO2-SH in the reaction mixture is 10g / L-100g / L, the concentration of HD monomer in the reaction mixture is 25g / L-100g / L, the concentration of PEGDA monomer in the reaction mixture is 25g / L-100g / L, the molecular weight of PEGDA monomer is 200g / mol-2000g / mol, and the concentration of DMPA in the reaction mixture is 0.5g / L-2g / L) is filled with nitrogen for 15 minutes, and then placed under ultraviolet light at 10w-60w for reaction for 2h-8h. After the reaction, the product is centrifuged and washed three times with anhydrous ethanol to obtain SiO2-g-PEGDA, which is a nanoparticle.
[0046] In some embodiments of the present invention, the steps of preparing a hybrid membrane using PVDF powder and SiO2-g-PEGDA are as follows: placing SiO2-g-PEGDA nanoparticles in N-methylpyrrolidone (NMP), ultrasonically dispersing, adding PVDF powder, heating at 60°C to dissolve, and standing for degassing for 24 hours to obtain a cast film, wherein the content of SiO2-g-PEGDA in the casting liquid is 0.2wt%-3wt%, and the content of PVDF powder in the casting liquid is 12wt%-20wt%; dropping the above casting liquid on a clean glass plate, and using a 50μm-500μm thick glass plate to coat the glass plate with a thickness of 1. The liquid flat film was obtained by scraping with a scraper, and the liquid flat film was immediately transferred to an artificial climate box (the temperature in the artificial climate box was 20°C-50°C, and the humidity was 30%-100%). After 10min-30min, the liquid flat film was taken out together with the glass plate, and immersed in a tris-HCl buffer solution containing dopamine (DA) at a concentration of 0.5g / L-4g / L, and reacted at room temperature for 6h-48h. After taking out, a PVDF hybrid membrane for oil-water separation was obtained, which was recorded as PVDF / SiO2-g-PEGDA / PDA hybrid membrane.
[0047] The principle of the present invention is: polyethylene glycol functionalized silica nanoparticles (SiO2-g-PEGDA) are hybridized with PVDF powder to prepare a casting solution, and a hybrid membrane with a rough surface structure can be prepared by combining a water vapor induced phase inversion method with an aqueous solution induced phase separation method. The nanoparticles introduced by the present invention can improve the pore structure, surface structure and pore hydrophilicity of the nanoparticles. At the same time, by introducing DA into the aqueous solution, a more hydrophilic polydopamine (PDA) layer can be coated on the rough membrane surface, thereby giving the separation membrane superhydrophilicity / underwater superoleophobicity.
[0048] The present invention uses a light-initiated mercapto-ene stepwise polymerization method to graft hydrophilic PEGDA onto SiO2 nanoparticles to obtain SiO2-g-PEGDA nanoparticles; the nanoparticles are further hybridized with PVDF powder, a flat membrane is prepared by a water vapor-induced phase conversion method, and after being immersed in a dopamine buffer solution for treatment, a hydrophilized hybrid membrane PVDF / SiO2-g-PEGDA / PDA is obtained. The hybrid membrane of the present invention has the characteristics of simple process and low cost, and the prepared hydrophilized hybrid membrane can be used as a sewage treatment separation membrane, and is particularly suitable for oil-water separation.
[0049] Unless otherwise specified, the room temperature in the present invention is 25±2°C.
[0050] All raw materials used in the examples and comparative examples of the present invention are purchased from commercial sources. For example, SiO2 nanoparticles are purchased from Shandong Xiya Chemical Co., Ltd.; PVDF powder is purchased from Shanghai San Ai Fu New Materials Co., Ltd., and the PVDF powder model is FR915.
[0051] It should be pointed out that the matters not described in detail in the present invention are conventional operating means in the art and are not the focus of the present invention.
[0052] The technical solution of the present invention is further illustrated by the following embodiments.
[0053] Example 1
[0054] (1) Synthesis of SiO2-g-PEGDA nanoparticles: 5 g of SiO2 nanoparticles (particle size of 50 nm) were weighed and placed in 100 mL of toluene. After ultrasonic dispersion for 30 min, 49.35 g of MPTS was added and refluxed at 110°C for 24 h. After the reaction was completed, the product was centrifuged and washed three times with anhydrous ethanol and dried to obtain SiO2-SH nanoparticles. 2 g of SiO2-SH nanoparticles were weighed and placed in a 150 mL quartz reaction flask. 20 mL of anhydrous ethanol was added and ultrasonic dispersion was performed for 15 min. Then, 1.5 g of HD, 0.0205 g of DMPA and 2 g of PEGDA monomer with a molecular weight of 400 g / mol were added in sequence. After nitrogen was filled for 15 min, the flask was sealed and transferred to a 30 W ultraviolet lamp for irradiation for 4 h. After the reaction, the product was centrifuged and washed three times with anhydrous ethanol and dried to obtain SiO2-g-PEGDA nanoparticles.
[0055] (2) Preparation of PVDF / SiO2-g-PEGDA0.05 / PDA hybrid membrane: 0.05 g of SiO2-g-PEGDA nanoparticles was weighed and placed in 10.5 g of NMP solvent. After ultrasonic dispersion for 15 min, 2 g of PVDF powder was added and heated and stirred at 60°C until completely dissolved. The mixture was allowed to stand for degassing for 24 h to obtain a casting solution. The casting solution was dropped onto a clean glass plate and a liquid film was scraped with a 200 μm scraper. The liquid film was quickly transferred to an artificial climate chamber at a temperature of 35°C and a humidity of 80%. After treatment for 20 min, a primary membrane was obtained. The primary membrane was immediately immersed in a tris-HCl buffer solution containing DA at a concentration of 2 g / L and treated at room temperature for 24 h. After being taken out, a PVDF hybrid membrane for oil-water separation was obtained, which was referred to as a PVDF / SiO2-g-PEGDA0.05 / PDA hybrid membrane and stored in pure water.
[0056] Figure 1The infrared spectra of SiO2 nanoparticles, SiO2-SH nanoparticles and SiO2-g-PEGDA nanoparticles in this embodiment indicate that SiO2-g-PEGDA has been successfully synthesized through the photochemical reaction of thiol-ene. In oil-water separation applications, the initial contact state of pure water of the membrane reflects the affinity of the membrane to water during initial use. Good hydrophilicity can make water molecules pass through the membrane pores more easily, thereby improving the flux and separation efficiency of the membrane; at the same time, hydrophilic membrane materials also have better anti-pollution properties because they can reduce the attachment of pollutants such as oil stains on the membrane surface. The initial contact angle of pure water of the PVDF / SiO2-g-PEGDA0.05 / PDA hybrid membrane prepared in this embodiment is 49.7°, which drops to 15.0° within 60s. It can be seen that when the membrane material prepared by the present invention contacts pure water, the membrane surface can quickly adsorb water molecules and expand them to form a uniform water film, indicating that the membrane material has good hydrophilicity and wettability. The membrane material of the present invention has excellent filtration efficiency and anti-pollution ability when used as an oil-water separation membrane.
[0057] Example 2
[0058] (1) Synthesis of SiO2-g-PEGDA nanoparticles: same as in Example 1;
[0059] (2) Preparation of PVDF / SiO2-g-PEGDA0.1 / PDA hybrid membrane: 0.1 g SiO2-g-PEGDA was weighed and placed in 10.5 g NMP solvent. After ultrasonic dispersion for 15 min, 2 g PVDF powder was added. The mixture was heated and stirred at 60°C until completely dissolved, and then allowed to stand for degassing for 24 h to obtain a casting solution. The casting solution was dripped onto a clean glass plate, and after the liquid film was scraped with a 200 μm scraping knife, the liquid film was quickly transferred to an artificial climate chamber at a temperature of 35°C and a humidity of 80%. After treatment for 20 min, the primary membrane was immediately immersed in a tris-HCl buffer solution containing DA at a concentration of 2 g / L. The membrane was treated at room temperature for 24 h, and then taken out to obtain a PVDF hybrid membrane for oil-water separation, which was recorded as a PVDF / SiO2-g-PEGDA0.1 / PDA hybrid membrane and stored in pure water.
[0060] The initial pure water contact angle of the PVDF / SiO2-g-PEGDA0.1 / PDA hybrid membrane prepared in this example was 31.8°, which decreased to 0° within 24 seconds.
[0061] Example 3
[0062] (1) Synthesis of SiO2-g-PEGDA nanoparticles: same as in Example 1;
[0063] (2) Preparation of PVDF / SiO2-g-PEGDA0.2 / PDA hybrid membrane: 0.2 g SiO2-g-PEGDA was weighed and placed in 10.5 g NMP solvent. After ultrasonic dispersion for 15 min, 2 g PVDF powder was added and heated and stirred at 60°C until completely dissolved. The mixture was allowed to stand for degassing for 24 h to obtain a casting solution. The casting solution was dropped onto a clean glass plate and a liquid film was scraped with a 200 μm scraper. The liquid film was then quickly transferred to an artificial climate chamber at a temperature of 35°C and a humidity of 80%. After treatment for 20 min, the primary membrane was immediately immersed in a tris-HCl buffer solution containing DA at a concentration of 2 g / L and treated at room temperature for 24 h. After being taken out, a PVDF hybrid membrane for oil-water separation was obtained, which was referred to as a PVDF / SiO2-g-PEGDA0.2 / PDA hybrid membrane and stored in pure water.
[0064] The initial pure water contact angle of the PVDF / SiO2-g-PEGDA0.2 / PDA hybrid membrane prepared in this example was 28.4°, which decreased to 0° within 10 s.
[0065] Example 4
[0066] (1) Synthesis of SiO2-g-PEGDA nanoparticles: same as in Example 1;
[0067] (2) Preparation of PVDF / SiO2-g-PEGDA0.3 / PDA hybrid membrane: 0.3 g SiO2-g-PEGDA was weighed and placed in 10.5 g NMP solvent. After ultrasonic dispersion for 15 min, 2 g PVDF powder was added and heated and stirred at 60°C until completely dissolved. The mixture was allowed to stand for degassing for 24 h to obtain a casting solution. The casting solution was dropped onto a clean glass plate and a liquid film was scraped with a 200 μm scraper. The liquid film was quickly transferred to an artificial climate chamber at a temperature of 35°C and a humidity of 80%. After treatment for 20 min, the primary membrane was immediately immersed in a tris-HCl buffer solution containing DA at a concentration of 2 g / L and treated at room temperature for 24 h. After being taken out, a PVDF hybrid membrane for oil-water separation was obtained, which was referred to as a PVDF / SiO2-g-PEGDA0.3 / PDA hybrid membrane and stored in pure water.
[0068] The pure water initial contact angle of the PVDF / SiO2-g-PEGDA0.3 / PDA hybrid membrane prepared in this example was 22.3°, which decreased to 0° within 9 seconds.
[0069] Comparative Example 1 Preparation of pure PVDF membrane
[0070] Weigh 2g of PVDF powder and place it in 10.5g of NMP solvent, and ultrasonicate it. Heat and stir at 60℃ until it is completely dissolved, and stand for degassing for 24h to obtain a casting solution. Drop the casting solution on a clean glass plate, and use a 200μm scraper to scrape the liquid film. Then quickly transfer the liquid film to an artificial climate box with a temperature of 35℃ and a humidity of 80%. After treating for 20min, the primary film is immediately immersed in pure water. When the separation film falls off the glass plate, take it out and store it in pure water.
[0071] The initial pure water contact angle of the PVDF powder film prepared in this comparative example was 124.4°, which decreased to 121.9° within 60 seconds.
[0072] Comparative Example 2 Preparation of PVDF / PDA membrane
[0073] Weigh 2g of PVDF powder and place it in 10.5g of NMP solvent, ultrasonicate, heat and stir at 60℃ until completely dissolved, and stand for degassing for 24h to obtain a casting solution. Drop the casting solution on a clean glass plate, scrape the liquid film with a 200μm scraper, and quickly transfer the liquid film to an artificial climate box with a temperature of 35℃ and a humidity of 80%. After treating for 20min, the primary membrane is immediately immersed in a tris-HCl buffer solution containing DA at a concentration of 2g / L. Treat at room temperature for 24h, take out the separation membrane, and store it in pure water.
[0074] The initial pure water contact angle of the PVDF / PDA membrane prepared in this comparative example was 73.2°, which dropped to 39.8° within 60 seconds.
[0075] Comparative Example 3 Preparation of PVDF / SiO2-g-PEGDA0.1 membrane
[0076] (1) Synthesis of SiO2-g-PEGDA nanoparticles: The synthesis method is the same as in Example (1);
[0077] (2) Preparation of PVDF / SiO2-g-PEGDA hybrid membrane: Weigh 0.1 g of SiO2-g-PEGDA and place it in 10.5 g of NMP solvent. After ultrasonic dispersion for 15 min, add 2 g of PVDF powder and heat and stir at 60°C until completely dissolved. Let it stand for degassing for 24 h to obtain a casting solution. The casting solution is dropped onto a clean glass plate. After the liquid film is scraped with a 200 μm scraper, the liquid film is quickly transferred to an artificial climate box with a temperature of 35°C and a humidity of 80%. After treatment for 20 min, the primary membrane is immediately immersed in pure water. When the separation membrane falls off the glass plate, it is taken out and stored in pure water.
[0078] The initial pure water contact angle of the PVDF / SiO2-g-PEGDA0.1 membrane prepared in this comparative example was 106.1°, which decreased to 99.6° within 60 seconds.
[0079] The above-mentioned examples and comparative examples show that the modified membrane has better hydrophilic properties than pure PVDF membrane and alkali-treated PVDF powder membrane.
[0080] Effect verification
[0081] (1) The surface morphology of the hybrid membrane was observed by scanning electron microscopy (SEM). Figure 2 (pure PVDF membrane), Figure 3 (PVDF / SiO2-g-PEGDA0.1), Figure 4 (PVDF / SiO2-g-PEGDA0.1 / PDA membrane) and Figure 5 As shown in (Example 3 PVDF / SiO2-g-PEGDA0.2 / PDA membrane), the morphological structure of the separation membrane can be regulated by adjusting the nanoparticle content and membrane forming conditions.
[0082] (2) Analysis of membrane surface wettability
[0083] The PVDF powder membrane in Comparative Example 1, the PVDF / PDA membrane prepared in Comparative Example 2, the PVDF / SiO2-g-PEGDA0.1 membrane prepared in Comparative Example 3, and the hybrid membranes prepared in Examples 1, 2, and 3 were used as experimental objects. 2 microliters of pure water was moved down from the syringe and contacted with the membrane surface until the water droplet was fully in contact with the membrane surface; then the syringe was lifted, and the results were as follows. Figure 6The results show that when a water drop is added to the PVDF powder film, its contact angle decreases from 124.4° to 121.9° within 60 seconds; when a water drop is added to the PVDF / PDA film, its contact angle decreases from 73.2° to 39.8° within 60 seconds; when a water drop is added to the PVDF / SiO2-g-PEGDA0.1 film, its initial contact angle is only 106.1°, and it decreases to 99.6° within 60 seconds; and when a water drop is added to the PVDF / SiO2-g-PE When the water droplets were added to the PVDF / SiO2-g-PEGDA0.1 / PDA membrane, the contact angle decreased from 31.8° to 0° within 24 seconds; when the water droplets were added to the PVDF / SiO2-g-PEGDA0.2 / PDA membrane, the contact angle decreased from 28.4° to 0° within 10 seconds, indicating that the hybrid membrane prepared by the present invention has super hydrophilic properties. The above results show that the hydrophilicity of the hybrid membrane prepared by Examples 1-3 of the present invention is significantly stronger than that of pure PVDF membrane, PVDF / PDA and PVDF / SiO2-g-PEGDA0.1 membrane.
[0084] The underwater contact angle of the separation membrane was further studied. During the experiment, the separation membrane was immersed in pure water, and then an oil droplet was squeezed out of the needle of the contact angle measuring instrument onto the membrane surface to measure its underwater oil contact angle value. The results are shown in Tables 1 and 2.
[0085] Table 1 Submersible pump oil contact angle of separation membrane
[0086] Sample name Contact angle value (°) PVDF powder 138.7 PVDF / PDA 152.8 <![CDATA[PVDF / SiO2-g-PEGDA0.1]]> 143.6 <![CDATA[PVDF / SiO2-g-PEGDA0.05 / PDA]]> 153.6 <![CDATA[PVDF / SiO2-g-PEGDA0.1 / PDA]]> 154.3 <![CDATA[PVDF / SiO2-g-PEGDA0.2 / PDA]]> 155.3
[0087] Table 2 Underwater oil contact angle of PVDF / SiO2-g-PEGDA0.1 / PDA separation membrane
[0088] Name of oil substance Contact angle value (°) Soybean Oil 155.1 Toluene 151.3 Petroleum ether 150.6
[0089] The above results indicate that the hybrid membrane prepared by the present invention has underwater superoleophobic characteristics.
[0090] (3) Determination of oil-water separation performance of membrane
[0091] The membranes prepared in Examples 1-3 and Comparative Examples 1-3 were used as experimental objects. The membrane samples were clamped in a membrane filtration tank, and the separation performance of the oil-water emulsion was measured at 0.03 MPa. The preparation method of the emulsion is as follows: 0.1 g of Tween 80 and 1.5 g of vacuum pump oil were weighed, added to 1000 mL of pure water, and ultrasonically treated for 60 min to obtain a milky white emulsion (i.e., pump oil emulsion). The separation performance of the oil-water emulsion was analyzed by comparing the optical photographs of the pump oil emulsion before and after separation. The retention rate data of the separation membrane are shown in Table 3.
[0092] Table 3 Emulsion separation performance of separation membrane
[0093] Membrane samples Retention rate (%) PVDF powder 92.9 PVDF / PDA 94.4 <![CDATA[PVDF / SiO2-g-PEGDA0.1]]> 96.0 <![CDATA[PVDF / SiO2-g-PEGDA0.05 / PDA]]> 98.5 <![CDATA[PVDF / SiO2-g-PEGDA0.1 / PDA]]> 98.4 <![CDATA[PVDF / SiO2-g-PEGDA0.2 / PDA]]> 94.0
[0094] The photos of the pump oil emulsion before and after separation by the PVDF / SiO2-g-PEGDA0.1 / PDA membrane prepared in Example 2 are shown in Figures 1 and 2. Figure 7 and Figure 8 As shown, by comparing the optical photographs of the pump oil emulsion before and after separation, it can be found that no oil droplets are distributed after separation, and the PVDF hybrid membrane prepared by the present invention has a good oil-water separation effect.
[0095] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a PVDF hybrid membrane for oil-water separation, characterized in that: The following steps are involved: Polyethylene glycol-functionalized SiO2 nanoparticles were synthesized by photoinitiated thiol-ene stepwise polymerization. The PVDF powder and the polyethylene glycol functionalized SiO2 nanoparticles are prepared into a casting solution, a primary hybrid membrane is prepared by a water vapor induced phase transformation method, and the primary hybrid membrane is immersed in a tris(hydroxymethyl)aminomethane hydrochloride buffer solution containing dopamine to obtain the PVDF hybrid membrane for oil-water separation.
2. The method for preparing a PVDF hybrid membrane for oil-water separation according to claim 1, characterized in that: The steps of synthesizing polyethylene glycol functionalized SiO2 nanoparticles are as follows: Treating SiO2 nanoparticles with 3-mercaptopropyltriethoxysilane to obtain mercaptolated SiO2 nanoparticles; Anhydrous ethanol is added to the thiolated SiO2 nanoparticles, and after uniform mixing, polyethylene glycol diacrylate, hexanedithiol and 2-dimethoxy-2-phenylacetophenone are added, and the mixture is reacted under ultraviolet conditions in a nitrogen atmosphere to synthesize polyethylene glycol functionalized SiO2 nanoparticles.
3. The method for preparing a PVDF hybrid membrane for oil-water separation according to claim 2, characterized in that: The mass ratio of the SiO2 nanoparticles to 3-mercaptopropyltriethoxysilane is (1-10): (5-50); And / or, when SiO2 nanoparticles are treated with 3-mercaptopropyltriethoxysilane: the treatment temperature is 80°C-120°C, and the treatment time is 12h-48h.
4. The method for preparing a PVDF hybrid membrane for oil-water separation according to claim 2, characterized in that: The mass ratio of the mercaptolated SiO2 nanoparticles, polyethylene glycol diacrylate, hexanediol and 2-dimethoxy-2-phenylacetophenone is (10-100): (25-100): (25-100): (0.5-2).
5. The method for preparing a PVDF hybrid membrane for oil-water separation according to claim 4, characterized in that: The molecular weight of the polyethylene glycol diacrylate is 200 g / mol-2000 g / mol.
6. The method for preparing a PVDF hybrid membrane for oil-water separation according to claim 2, characterized in that: When reacting under ultraviolet conditions: the power of ultraviolet light is 10w-60w, and the reaction time is 2h-8h.
7. The method for preparing a PVDF hybrid membrane for oil-water separation according to claim 1, characterized in that: The steps of preparing PVDF powder and the polyethylene glycol functionalized SiO2 nanoparticles into a casting solution are as follows: placing the polyethylene glycol functionalized SiO2 nanoparticles in N-methylpyrrolidone, ultrasonically dispersing, adding PVDF powder, heating to dissolve, and standing to degas to obtain the casting solution.
8. The method for preparing a PVDF hybrid membrane for oil-water separation according to claim 7, characterized in that: The content of polyethylene glycol functionalized SiO2 nanoparticles in the casting solution is 0.2wt%-3wt%, and the content of PVDF powder in the casting solution is 12wt%-20wt%.
9. A PVDF hybrid membrane for oil-water separation, characterized in that: Prepared according to the method according to any one of claims 1 to 8.
10. Use of the PVDF hybrid membrane for oil-water separation according to claim 9 in oil-water separation.